Praktikalitas LKPD Eksperimen Biologi Berorientasi Keterampilan Proses Sains untuk Pesereta Didik SMA Kelas XI Semster 1 - Mitha Safitri; Helendra Helendra; Ganda Hijrah Selaras; Ramadhan Sumarmin (Bioilmi: Jurnal Pendidikan, 2019)
Biology learning is one of the subjects that involves practicum in the laboratory. This activity aims to develop the scientific process skills possessed by students in conducting practicum, so that the method used to guide and direct students with the use of students worksheet biological experiment. The results of observations made, it is known that the science process skills possessed by students are still relatively low and the availability of experimental students worksheet has not been implemented. That is why the students worksheet of biological experimentation oriented scientific process skills for students class XI semester 1. The type of this research is development research using 4D models, namely define, design, develop, and disseminate. This study discusses about the development stage, namely the practicality of experimental students worksheet. The instrument used a practicality test questionnaire given to teachers and students. The questionnaire was given to two teachers and 32 students in terms of four aspects, namely the ease of use of the experimental students worksheet, the allocation of implementation time, the ease of interpretation and equilibrium. The data obtained from the results of the practicality questionnaire analysis by two teachers on the experimental students worksheet oriented scientific proess skills had an average value of 4.00 categorized as very practical. The results of the practicality questionnaire analysis by 32 students of the experimental students worksheet oriented scientific process skills obtained an average value of 3.67 categorized as very practical. So, it can be concluded that the experimental students worksheet oriented scientific proess skills is very practical to use.